1981
DOI: 10.1007/bf02377116
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and elemental uptake in fertilized and unfertilizedBetula papyrifera Marsh. andPopulus grandidentata Michx.

Abstract: SUMMARYEstimates were made of the above-ground biomass and contents of N, P, K, Ca, Mg, Mn, Na, Fe, Zn, A1, and Cu in fertilized (N 448 kg/ha, P 112 kg/ha, lime 4480 kg/ha) and unfertilized white birch (Betula papyrifera Marsh,) and bigtooth aspen (Populus grandidentata Michx.). For individuals of both species, fertilization increased the average above-ground biomass increment and the N and P content increment by 150 per cent and 300 per cent, respectively, but decreased uptake of Mn and Zn. The allocation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…In aboveground compartments, iron was present in higher concentrations in the leaves and trunk bark of red maple and white birch trees in the constructed wetland and the reference site in August 2006. Higher concentrations of iron in the leaves and trunk bark of mature white birch trees were also observed by Schmitt et al [46] and Young and Guinn [40] . Morrison and Hogan [42] and Pastor and Bockheim [37] observed higher concentrations of iron in the leaves and trunk bark of sugar maple trees in Ontario and Northern Wisconsin, respectively.…”
Section: Branchessupporting
confidence: 70%
See 2 more Smart Citations
“…In aboveground compartments, iron was present in higher concentrations in the leaves and trunk bark of red maple and white birch trees in the constructed wetland and the reference site in August 2006. Higher concentrations of iron in the leaves and trunk bark of mature white birch trees were also observed by Schmitt et al [46] and Young and Guinn [40] . Morrison and Hogan [42] and Pastor and Bockheim [37] observed higher concentrations of iron in the leaves and trunk bark of sugar maple trees in Ontario and Northern Wisconsin, respectively.…”
Section: Branchessupporting
confidence: 70%
“…Morrison and Hogan [42] , Schmitt et al [46] and Wittwer et al [43] observed a 2.8 fold, 3.3 fold and a 9.2 fold increase in the concentrations of iron in the trunk bark of sugar maple, white birch and red pine trees, respectively compared to the trunk wood concentrations. Young and Guinn [40] observed a 5.9 fold, 5.5 fold and a 5.0 fold increase in the concentrations of iron in the trunk bark of red spruce, white birch and red maple trees, respectively compared to the trunk wood concentrations.…”
Section: Iron Distribution Within Treesmentioning
confidence: 94%
See 1 more Smart Citation
“…Some have reported increased foliar P concentrations with fertilization (Mercer 1974;Safford and Filip 1974;Ellis 1979;Safford and Czapowskyj 1986;Fahey et al 1998;Gradowski and Thomas 2008), indicating that fertilization did significantly increase P availability. However, others (Finn and White 1966;Schmitt et al 1981;Leech and Kim 1990;Ouimet and Fortin 1992) found no such increase, which is consistent either with Psufficiency in the control trees, or with insufficient P availability relative to other added nutrients.…”
Section: Production Responses To P Fertilizationmentioning
confidence: 70%
“…These values are comparable to data reported in the literature. Morrison and Hogan [34] , Schmitt et al [35] and Wittwer et al [36] observed average manganese concentrations of 264-411, 543 and 304 mg kg 1 in the branches of sugar maple, white birch and red pine trees, respectively. Young and Guinn [25] observed average manganese concentrations of 830, 273 and 1076 mg kg 1 in the branches of red maple, white birch and red spruce trees, respectively.…”
Section: Branchesmentioning
confidence: 96%